The biosynthesis of the anti‐microbial diterpenoid leubethanol in Leucophyllum frutescens proceeds via an all‐cis prenyl intermediate. (28th August 2020) - Miller, Garret P.; Bhat, Wajid Waheed; Lanier, Emily R.; Johnson, Sean R.; Mathieu, Davis T.; Hamberger, Björn
SUMMARY: Serrulatane diterpenoids are natural products found in plants from a subset of genera within the figwort family (Scrophulariaceae). Many of these compounds have been characterized as having anti‐microbial properties and share a common diterpene backbone. One example, leubethanol from Texas sage ( Leucophyllum frutescens ) has demonstrated activity against multi‐drug‐resistant tuberculosis. Leubethanol is the only serrulatane diterpenoid identified from this genus; however, a range of such compounds have been found throughout the closely related Eremophila genus. Despite their potential therapeutic relevance, the biosynthesis of serrulatane diterpenoids has not been previously reported. Here we leverage the simple product profile and high accumulation of leubethanol in the roots of L .  frutescens and compare tissue‐specific transcriptomes with existing data from Eremophila serrulata to decipher the biosynthesis of leubethanol. A short‐chain cis ‐prenyl transferase ( Lf CPT1) first produces the rare diterpene precursor nerylneryl diphosphate, which is cyclized by an unusual plastidial terpene synthase ( Lf TPS1) into the characteristic serrulatane diterpene backbone. Final conversion to leubethanol is catalyzed by a cytochrome P450 (CYP71D616) of the CYP71 clan. This pathway documents the presence of a short‐chain cis ‐prenyl diphosphate synthase, previously only found in Solanaceae, which is likely involved in the biosynthesis of other known diterpene backbones in Eremophila . Lf TPS1 represents neofunctionalization of a compartment‐switching terpene synthase accepting a novel substrate in the plastid. Biosynthetic access to leubethanol will enable pathway discovery to more complex serrulatane diterpenoids which share this common starting structure and provide a platform for the production and diversification of this class of promising anti‐microbial therapeutics in heterologous systems. Significance Statement: Serrulatane diterpenoids are natural products known for their anti‐microbial activities, and access is currently limited to chemical synthesis or extraction from natural sources. Here we report the full biosynthetic pathway to the serrulatane diterpenoid leubethanol from Leucophyllum frutescens, which is active against multi‐drug‐resistant tuberculosis. The pathway involves an uncommon diterpene precursor, and further steps yield the archetypal diterpenoid structure shared across nearly all serrulatanes, which may enable development of a new class of anti‐microbial therapeutics.